2003
DOI: 10.1203/01.pdr.0000061564.86797.78
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hypertrophy and Altered Hemodynamic Adaptation in Growth-Restricted Preterm Infants

Abstract: The objective was to elucidate hemodynamic adaptation in very low birth weight (Ͻ1500 g) infants after intrauterine growth retardation. 31 growth-retarded (SGA, birth weight Ͻ-2 SD) and 32 appropriate for gestational age (AGA, birth weight within Ϯ 1 SD range) infants were enrolled. In SGA infants, the diastolic diameters of the interventricular septum and the left ventricle were increased, and serum brain natriuretic peptide (BNP) was elevated. Left ventricular output (LVO) of the AGA infants increased from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 26 publications
10
51
1
4
Order By: Relevance
“…It was suggested that the increased cardiac size in IUGR fetuses could be due to a 'sparing effect'. A study published by Leipala et al 7 also found increased cardiac size in growth-restricted preterm infants and suggested that such findings may be due to in utero changes of peripheral vascular resistance in accordance with the 'brain-sparing' effect of IUGR. It has also been shown that maternal undernutrition from early-to mid-gestation leads to cardiac hypertrophy in fetal sheep.…”
Section: Discussionmentioning
confidence: 87%
“…It was suggested that the increased cardiac size in IUGR fetuses could be due to a 'sparing effect'. A study published by Leipala et al 7 also found increased cardiac size in growth-restricted preterm infants and suggested that such findings may be due to in utero changes of peripheral vascular resistance in accordance with the 'brain-sparing' effect of IUGR. It has also been shown that maternal undernutrition from early-to mid-gestation leads to cardiac hypertrophy in fetal sheep.…”
Section: Discussionmentioning
confidence: 87%
“…Secondly, the subjects who were included in the previous studies were healthy full term infants and preterm infants, populations which were different from those of our study. Thirdly, recent studies have demonstrated that foetuses and newborns with severe forms of growth restriction have significant changes in their cardiac function parameters [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…There is also a need of following up these cardiac blood flow measurements serially, throughout infancy, at regular intervals, to know the correlation of these flows with adult onset cardiovascular disease. Barker's hypothesis on foetal programming of adult disease mainly emphasizes on SGA neonates and recent studies have demon strated that foetuses and newborns with severe forms of growth restrictions have significant changes in foetal cardiac function parameters [19][20][21]. The functional echocardiography parameters in these SGA neonates would be non-invasive clinical parameters, which will help in serial monitoring of their cardiovascular statuses in various disease states.…”
Section: Resultsmentioning
confidence: 99%
“…Recently a study in patients with congenital heart defects amenable to biventricular repair indicated that measurement of circulating levels of BNP can predict the development of low cardiac output syndrome (LCOS) and prolonged mechanical ventilation (5).Furthermore, other studies indicated higher plasma level of BNP in children with congenital heart disease and newborns with severe fetal distress (6)(7)(8).Because of serious complications related to congenital cardiac defects, surgical repair or palliation of congenital cardiac defects is carried out usually during the neonatal period (8)(9).Moreover, neonates,compared to infants and children, have more adverse events and perioperative mortality.…”
mentioning
confidence: 99%
“…On the other hand,the clinical predictive value of perioperative plasma BNP levels in neonates, who are most at risk for unpredictable adverse outcomes, is controversial [5][6][7][8][9][10] . So, we steered this study to address these concerns and to shed light on predictive value of preoperativeBNP plasma level in patients under cardiac surgery .…”
mentioning
confidence: 99%